(untitled) (Pesquisa Odontológica Brasileira, 2001)
The aim of this study was to evaluate the incidence of postoperative pain and the type of periapical repair, after one-appointment endodontic treatment in asymptomatic patients who presented with pulpal necrosis and radiographically visible chronic periapical lesions. For that, after biomechanical preparation through the step down followed by the step back technique, aided by copious irrigation with 5.0% sodium hypochlorite solution, the filling of the root canals was carried out through the conventional technique, with gutta-percha cones and zinc oxide-eugenol cement. In the immediate postoperative period, 16.6% of all patients presented with spontaneous pain, although the incidence of severe pain - flare-ups - was 3.3%. After twelve months, all patients were asymptomatic and free of fistula, nevertheless only 46.4% exhibited complete resolution of the radiolucent periapical areas. Therefore, in a medium term, the one-appointment endodontic treatment showed 100% of clinical success, but showed a reduced rate of radiographic success.